Design and fabrication of firing test rig for two-stroke spark ignition engine - Mohd Fadhil, Rani (2008)
The two-stroke engine is widely used in motorcycle especially in motorcycle racing and also for the kart engine. The mechanical simplicity of the two-stroke engine gives it great power, and makes it a tempting target for tuning operations. The key to successful design, development and modification is knowledge of the engine's operating principles itself [8]. A firing of engine test rig built specifically for high speed application is design for two strokes spark ignition engine to allow further study and have better understanding of flow mechanism of the engine at high speed condition. This project represents the experimentally testing for two-stroke spark ignition engine and the method of measurement for the engine. The objective of this project is to design and fabrication of firing test rig for two-stroke spark ignition engine. The first step is design and modeling of the engine test rig using the SolidWork 2005 software. Then, after the design have been finalize, the fabrication process will take place to mount the engine and also all the equipment needed during the testing. For fuel consumption measurement, the data will completely using a gravimetric method and for air consumption measurement, the data will be are measuring using the airbox method respectively.